2020
DOI: 10.1136/bmjqs-2019-010534
|View full text |Cite
|
Sign up to set email alerts
|

Valuing hospital investments in nursing: multistate matched-cohort study of surgical patients

Abstract: BackgroundThere are known clinical benefits associated with investments in nursing. Less is known about their value.AimsTo compare surgical patient outcomes and costs in hospitals with better versus worse nursing resources and to determine if value differs across these hospitals for patients with different mortality risks.MethodsRetrospective matched-cohort design of patient outcomes at hospitals with better versus worse nursing resources, defined by patient-to-nurse ratios, skill mix, proportions of bachelors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 43 publications
2
31
0
1
Order By: Relevance
“…Economic performance was evaluated using a measure of 30-day resource utilizationbased costs, which were inflation-adjusted and computed from the costs of resources used during the in-hospital admission as well as any costs accrued 30-days post-admission (Appendix 4). 5,6,13,14 If a patient was readmitted within 30 days of the index admission date, all costs accrued during the readmission (including in-patient costs beyond 30 days) were included. Inhospital costs are a function of length of stay, level of care (i.e., ICU vs. general unit), 15 and total relative value units from bills.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Economic performance was evaluated using a measure of 30-day resource utilizationbased costs, which were inflation-adjusted and computed from the costs of resources used during the in-hospital admission as well as any costs accrued 30-days post-admission (Appendix 4). 5,6,13,14 If a patient was readmitted within 30 days of the index admission date, all costs accrued during the readmission (including in-patient costs beyond 30 days) were included. Inhospital costs are a function of length of stay, level of care (i.e., ICU vs. general unit), 15 and total relative value units from bills.…”
Section: Discussionmentioning
confidence: 99%
“…We defined study hospitals as having either better or worse nursing resources using a coherence rank score based on four aspects of nursing (i.e., staffing, skill mix, education, work environment) (Appendix 5). 6,17 The four aspects of nursing within each of the 512 study hospitals were compared to all other hospitals to compute a score for every hospital using coherence methods. 18 In brief, each hospital was assigned a score between 1 and 512 and rank-ordered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated the association between acute status and other patient and organizational measures, and nurse-sensitive outcomes such as mortality and the AE studied here. Nevertheless, further studies are required that combine acuity and complexity measures, as well as organizational variables such as nurse staffing or missed care, to gain a better understanding of their role in patient outcomes [56][57][58].…”
Section: Plos Onementioning
confidence: 99%